Philosophers and Friends - Emmet, Dorothy. author. aut Link
XIV, 130 p.
Keywords: With a wealth of anecdote Dorothy Emmet looks back on the philosophers who made a personal impact on her. She brings to life the Oxford of the 1920s, and writes particularly about H.A. Pritchard and R.G. Collingwood. She knew A.N. Whitehead and Samuel Alexander, and remembers philosophers who struggled with political dilemmas when a number of intellectuals were turning to Marxism. Describing the post-war period she recalls R.B. Braithwaite, Michael Polanyi, Alasdair MacIntyre and others. Her personal portraits will interest a wide readership, as well as making essential reading for professional philosophers.